Respuesta :
hello :
f(x) = (x – 1)(x + 6)
f(x) =0
(x – 1)(x + 6) = 0
x-1=0 or x+6=0
x=1 or x= -6.....(answers : B and D)
f(x) = (x – 1)(x + 6)
f(x) =0
(x – 1)(x + 6) = 0
x-1=0 or x+6=0
x=1 or x= -6.....(answers : B and D)
The zeros of the function f(x) = (x – 1)(x + 6) are option (B) x = 1 and (D) x = -6 are the correct answers.
What is a quadratic equation?
A quadratic equation is a polynomial which has the highest degree equal to two. It is a second-degree equation of the form ax² + bx + c = 0, where a, b, are the coefficients, c is the constant term, and x is the variable.
For the given situation,
The function is f(x) = (x – 1)(x + 6)
The zeros of a function are the values of x at which the total equation is equal to zero.
[tex]f(x) = (x -1)(x + 6)[/tex]
To find zeros equate each factors to zero,
[tex]x-1=0[/tex]
⇒ [tex]x=1[/tex]
[tex]x+6=0[/tex]
⇒ [tex]x=-6[/tex]
Hence we can conclude that the zeros of the function f(x) = (x – 1)(x + 6) are option (B) x = 1 and (D) x = -6 are the correct answers.
Learn more about quadratic equation here
https://brainly.com/question/12014272
#SPJ3